Validation of the CALL score as a mortality prediction tool in a cohort of hospitalized COVID-19 patients in Chile - Sanhueza, Matías; Barrera, Manuel; Pedemonte, Juan C.; Rojas, Luis (Frontiers in Medicine, 2023)
Introduction The CALL score is a predictive tool for respiratory failure progression in COVID-19. Whether the CALL score is useful to predict short- and medium-term mortality in an unvaccinated population is unknown. Materials and methods This is a prospective cohort study in unvaccinated inpatients with a COVID-19 pneumonia diagnosis upon hospital admission. Patients were followed up for mortality at 28 days, 3, 6, and 12 months. Associations between CALL score and mortality were analyzed using logistic regression. The prediction performance was evaluated using the area under a receiver operating characteristic curve (AUROC). Results A total of 592 patients were included. On average, the CALL score was 9.25 (±2). Higher CALL scores were associated with increased mortality at 28 days [univariate: odds ratio (OR) 1.58 (95% CI, 1.34–1.88), p < 0.001; multivariate: OR 1.54 (95% CI, 1.26–1.87), p < 0.001] and 12 months [univariate OR 1.63 (95% CI, 1.38–1.93), p < 0.001; multivariate OR 1.63 (95% CI, 1.35–1.97), p < 0.001]. The prediction performance was good for both univariate [AUROC 0.739 (0.687–0.791) at 28 days and 0.869 (0.828–0.91) at 12 months] and multivariate models [AUROC 0.752 (0.704–0.8) at 28 days and 0.862 (0.82–0.905) at 12 months]. Conclusion The CALL score exhibits a good predictive capacity for short- and medium-term mortality in an unvaccinated population.